Digital Marketing Implementation in the Handicraft Industry - Azizah, Adelia Rizki Nur; Nurdima, Fildzah; Febrianti, Nurlia; Prasetyo, Johan Hendri; Aisyah, Aisyah (JURNAL KEWIRAUSAHAAN, AKUNTANSI DAN MANAJEMEN TRI BISNIS, 2025)
The advancement of digital technology encourages entrepreneurs, including MSMEs in the handicraft sector, to adapt through relevant and effective marketing strategies. This study examines the implementation of digital marketing at Arna Decor, a student-run business specializing in MDF wood-based home decoration. The background of this research is based on the limited utilization of digital media by business owners, such as inconsistency in visual content on social media and the suboptimal use of digital promotion features. This study aims to evaluate the digital marketing strategies implemented and their impact on brand awareness and sales performance. A descriptive qualitative method with a case study approach was used. Data were collected through direct observation, documentation of social media and marketplace insights, and relevant literature studies. The strategies implemented include visual storytelling on social media (Instagram and TikTok), optimization of paid advertising on marketplaces (Shopee, Tokopedia, TikTok Shop), and promotional expansion through affiliate programs. The results show significant improvements: Instagram profile visits increased by 155.6%, TikTok content views grew, and sales on marketplaces rose consistently. The effectiveness of these strategies is reflected in the ROAS ratio of 4.77 on Shopee Ads and an ROI of 43.7 in Shopee's affiliate program. Positive customer reviews further reinforced trust in the brand. It can be concluded that structured and consistent digital marketing implementation can enhance visibility, market reach, and brand image in the handicraft industry.